2017
DOI: 10.1073/pnas.1606948114
|View full text |Cite
|
Sign up to set email alerts
|

Two types of amorphous protein particles facilitate crystal nucleation

Abstract: Nucleation, the primary step in crystallization, dictates the number of crystals, the distribution of their sizes, the polymorph selection, and other crucial properties of the crystal population. We used timeresolved liquid-cell transmission electron microscopy (TEM) to perform an in situ examination of the nucleation of lysozyme crystals. Our TEM images revealed that mesoscopic clusters, which are similar to those previously assumed to consist of a dense liquid and serve as nucleation precursors, are actually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
165
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 36 publications
(39 reference statements)
15
165
2
Order By: Relevance
“…This has been concluded by Yamazaki et al [56] (who conducted experiments with LC-TEM). The authors have established that mesoscopic clusters, similar to those previously assumed to consist of a dense liquid and serve as nucleation precursors, are not liquid but amorphous solid particles consisting of lysozyme molecules.…”
Section: Evoking Nucleation; Classical Nucleation Theory (Cnt) Vs Musupporting
confidence: 55%
See 1 more Smart Citation
“…This has been concluded by Yamazaki et al [56] (who conducted experiments with LC-TEM). The authors have established that mesoscopic clusters, similar to those previously assumed to consist of a dense liquid and serve as nucleation precursors, are not liquid but amorphous solid particles consisting of lysozyme molecules.…”
Section: Evoking Nucleation; Classical Nucleation Theory (Cnt) Vs Musupporting
confidence: 55%
“…For instance, Yamazaki et al [56] have used LC-TEM to understand the mechanisms underlying the early stages of protein crystallization (see Section 2.1).…”
Section: Introductionmentioning
confidence: 99%
“…All experimental data for the dimensionless supersaturations studied (numbers on right-hand side) fall on the orange logistic curves (for the color references, refer to the web version of this article). The dashed straight lines with coordinates (00), (11) are a guide for the eye only; it is seen that the experimental points less than t/t p = 0.5 are situated below the dashed straight line, while the points for greater t/t p values (up to 1) lie above this line. Experimental data are plotted for: (a) bulk nucleation; (b) on-glass nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the relative efficiencies of the various pathways leading towards the final crystalline state have been studied. Most recently, direct transition electron microscopic observations of Yamazaki et al [11] have suggested a significant departure from the initial TSNM assumption. The authors have never observed formation of crystalline phases inside amorphous solid particles consisting of lysozyme molecules, which are like those previously assumed to consist of a dense liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, recent experimental measurements of nucleation rates revealed that they are even lower, by many orders of magnitude, than those predicted by theory (19)(20)(21). The issue of low nucleation rates and several other unexplained features of protein nucleation kinetics was resolved by the discovery that the nuclei of ordered protein solids form not in the supersaturated solution but rather in preexisting mesoscopic protein-rich clusters (22)(23)(24)(25)(26)(27)(28)(29)(30). In addition to crystals, the mesoscopic clusters host the nucleation of other ordered protein solids, such as sickle-cell hemoglobin polymers (27) and amyloid fibrils (28)(29)(30).…”
Section: Introductionmentioning
confidence: 97%